PS 05-69 PREDICTORS OF HIGH AORTA BLOOD PRESSURE IN YOUNG MEN WITH ISOLATED SYSTOLIC HYPERTENSION. (September 2016) - Radchenko, Ganna; Torbas, Olena; Sirenko, Yuriy; Snitzarenko, Olena
Abstract : Objective: According to ECS|ESH-2013 guildelines isolated systolic hypertension (ISH) in young state needs aorta blood pressure (BP) evaluation, but using of special devices is not common. We try to evaluate the clinical predictors of high aorta BP in young men with ISH. Design and Method: There were included 44 young men (mean age 32.2 ± 1.3yrs) with ISH (mean systolic(SBP)|diastolic(DBP) BP 153.4 ± 2.1|86.9 ± 1.7mmHg), whom were done office and 24-h (for exclusion of white coat hypertension) BP measurements, central SBP (cSBP) and pulse wave velocity (PWV) evaluations by Sphygmocor, ECG, EchoCG, anthropometric measurements. Multifactorial regression and incremental analysis were used for evaluation of the high aorta SBP predictors. Results: There were found that among ISH men 17 (38.6%) had normal cSBP (<125 mmHg). In comparison with high cSBP pts, they were characterized by less age (28.2 ± 1.7 vs 34.7 ± 1.6yrs, p = 0.012), more height (186.5 ± 1.6 vs 176.3 ± 1.8 cm, p < 0.001), less BMI (25.2 ± 0.7 vs 29.7 ± 0.8 kg|m 2, p = 0.001), lower level of office SBP (146.1 ± 1.7 vs 156.5 ± 2.7mmHg, p < 0.002), but no 24-h SBP (137.7 ± 1.8 vs 138.8 ± 2.4 mmHg, NS), lower aorta PWV (9.3 ± 0.5 vs 11.2 ± 0.5 m|s, p = 0.019). No any other significant differences were found. The presence of high cSBP was correlated with age (r = 0.31, p = 0.04), height (r = −0.30, p < 0.05), weight (r = 0.32, p < 0.034), BMI (r = 0.45, p = 0.002), office SBP (r = 0.38, p < 0.01) and DBP (r = 0.57, p = 0.001). After incremental regression analysis there were found that independent predictors were height < 178 cm (β = 7.038, p = 0.05), weight > 91 kg (β = 5.53, p = 0.033) and office DBP > 80mmHg (β = 4.43, P = 0.05). Two or three predictors were found in 85.2% pts with higher cSBP and only in 17.6% pts with normal sSBP. Conclusions: In 38.6% of young men with ISH the aorta SBP is normal. The predictors of high cSBP in young men with ISH were height < 178 cm, weight > 91 kg and office DBP > 80mmHg. Patients with office ISH and two or three these factors could be treated without aorta BP evaluation.